Assessing The Correlation Between Smartphone Usage, Learning Autonomy, And Foreign Language Acquisition in Children - Putra, Rizky Anugrah (Yayasan Nurul Iman Muara Gading Mas, 2024)
Various opinions exist regarding the use of smartphones and their effects on children's language acquisition. While some suggest that smartphones can positively influence learning habits and language skills, others argue they may have negative consequences. To explore this issue, a correlational study was conducted to assess the relationship between smartphone usage, self-directed learning (SDL), and foreign language acquisition (FLA). A questionnaire with 12 Likert-scale questions was administered to 29 parents of children aged 5 to 7 years. Following the collection and quantification of the data through correlation analysis, the researcher discovered that, although there was no significant correlation between smartphone usage and either SDL or FLA, a meaningful and significant relationship was identified between SDL and FLA. This finding suggests that children who exhibit effective self-directed learning behaviors are likely to achieve optimal outcomes in foreign language acquisition.